Magnetic field effects on the valence band of AlGaAs and InGaAsP parabolic quantum wells - Tito Patricio, M. A.; Villegas-Lelovsky, L. [UNESP]; Cardozo de Oliveira, E. R.; Marques, G. E.; LaPierre, R. R.; Toropov, A. I.; Pusep, Yu. A. (American Physical Society (APS), 2023)
The influence of the valence band structure on the optical properties of quantum wells with a parabolic potential, consisting of Formula Presented and Formula Presented alloys, is studied and compared. The distribution of photogenerated carriers over the parabolic potential is found to be responsible for specific selection rules: the recombination due to only odd-indexed confined levels is observed. The reason for this is the accumulation of photogenerated holes at the center of the parabolic potential, which results in interband electron-hole recombination occurring at the center of the parabolic quantum wells. Furthermore, a specific valence band structure is found to be responsible for the magnetic-field-induced change in the photoluminescence circular polarization. In particular, at a certain magnetic field, the hybridization of the states of a heavy hole and a light hole results in the intersection of Landau levels with different spins, which leads to the observed change in the circular polarization of photoluminescence. The processes of long-term spin relaxation of heavy holes in both studied parabolic quantum wells are demonstrated, and the corresponding times are obtained.